Introducing a 4-pyridyl group on the backbone of polybenzoxazine to an analog fixed-DMAP catalyst. (15th August 2021) - Guo, Tianfo; Tong, Haoying; Li, Zhenjiang; Sun, Jie; Li, Yongqiang; Yan, Rui; Liu, Bo; Zhang, Zhihao; Zhu, Yuejia; Guo, Kai
Graphical abstract: Highlights: Polybenzoxazine anchored pyridyl moiety as organocatalyst was firstly proposed. The polybenzoxazine was evaluated as nucleophilic catalyst in acylation reaction. The catalyst was comparable to commercial PS-DMAP in catalysis and in recycles. Abstract: Polybenzoxazine (PBz) anchored with an N -4′-pyridyl group on the backbone was prepared and characterized. Phenolic-type polybenzoxazine was selectively prepared by thermally initiated ring-opening polymerization of N -(4′-pyridyl)benzoxazine (Bz-Py). The loading of the catalytic moiety pyridyl on PBz-Py was 2.7 mmol g −1 . The catalytic comparison of the prepared PBz-Py to commercial PS-DMAP in acylation reactions was investigated. The catalytic PBz-Py showed a broad scope of substrates of sterically hindered secondary and tertiary alcohols, aniline, quinoline, and steroid at room temperature within two hours by high yields up to 96%. Further extension to PBz-Py-catalyzed silylation and tritylation reactions resulted in high yields. The catalyst retained 85% activity after 4 recycles. The implementation of a 4-pyridyl group on the PBz backbone as a new type of polymeric catalyst showcased a general manifold to introduce catalytic moieties to designed polybenzoxazine catalysts.